Policy co-ordination and growth traps in a middle-income country setting: The case of South Africa - Haroon Bhorat; Aalia Cassim; Alan Hirsch (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
South Africa has exhibited tepid economic growth over the past twenty years as well as high levels of income inequality characteristic of a middle income country growth trap. This paper compares and contrasts South Africa's growth trap relative to middle-income peer economies. In addition, we study the policies and structures of the South African economy that have indeed perpetuated the persistently low levels of growth observed. In particular we consider the capital-intensive nature of manufacturing, regulation in the telecommunication and transport sector and the inadequacies of Black Economic Empowerment policies. The paper concludes discussing the welfare outcomes on the vast majority of South Africans who are unable to participate in the economy.
Keywords: O10; O20; O25; O40; 330; South Africa; growth trap; middle income country; policy co-ordination; industrial policy